Computer hazard: A potential impediment to the growth of ICT in Nigeria - Abdulfattah, A. A.; Rakiya, A. M.; Abdulfattah, B. M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2008)
The well-orchestrated new millennium (year 2000) problem in computer-based economy has gone without any noticeable negative imprint as envisaged, and computer users have had sigh of relief. With Information and Communication Technology (ICT) still dictating pace in many sectors, the number of computer users is on the increase with full readiness to exploit all possible gains of this information age.  In this paper, the authors bring into limelight health implication of the increase in computer application as a result of electromagnetic radiation from the monitor coupled with the attitude of computer users in Nigeria and the negative influence it could have on the application of ICT facilities in the country if not quickly tackled.